Detective Knight. Rogue [videorecording (DVD)] - Drake, Edward; Large, Corey; Large, Corey; Willis, Bruce, 1955-; Munro, Lochlyn, 1966-; Jean-Louis, Jimmy, 1968- (Lionsgate, 2022)
Veteran detective Hames Knight is dedicated to navigating the demanding streets of Los Angeles, in this thrilling first of a trilogy of films. As the city prepares for Halloween, mask-wearing armed robbers critically wound Knight's partner in a shootout following a heist. With Knight in hot pursuit, the bandits flee L.A. for New York, where the detective's dark past collides with his present case and threatens to tear his world apart, unless redemption can claim Knight first.